Preliminary Steps of Urban Farming Spatial Database Development for SDGs Monitoring and Evaluation in Bogor City - Dwikorawati, Syarifah Sofiah; Wicaksono, Arif; Susetyo, Budi (Jurnal Manajemen, 2023)
The mandate of Presidential Regulation 111/2022 states that the Sustainable Development Goals (SDGs) need to be synchronized with the five-year National Development Plan (RPJMN) at the central government level, and the five-year Regional Development Plan (RPJMD) at the provincial and city/district levels. Further synchronization at the national level will eventually be completed in the National Action Plan (RAN), while at the provincial/city/district level it will produce a Regional Action Plan (RAD). This study aims to prepare the first steps for the development of urban agriculture spatial databases to support the monitoring and evaluation of SDGs and the formulation of RAD in Bogor City. The method used is a descriptive method through a Focus Group Discussion (FGD) with a synchronization analysis between the SDGs and the five-year development plan (RPJMD) of Bogor City 2019-2024. The FGD activity was also attended by 114 representatives of women's farmer groups (KWT). The results of the analysis show that the development of a spatial database of urban agriculture to support the subsequent monitoring and evaluation of SDGs in Bogor City was carried out through an analysis of the role of KWT locations in poverty reduction within a certain radius in each KWT plantation location. This can be an indication that urban farming spatial databases can be used to evaluate SDGs 1 (No Poverty) and 2 (No Hunger).